Multiscale modeling to evaluate combined effect of covalent grafting and clustering of silica nanoparticles on mechanical behaviors of polyimide matrix composites - Baek, Kyungmin; Park, Hyungbum; Shin, Hyunseong; Yang, Seunghwa; Cho, Maenghyo (ELSEVIER SCI LTD, 2021)
A multiscale model was developed to simultaneously investigate the effect of covalent grafting and clustering of silica nanoparticles on the mechanical behaviors of polyimide nanocomposites. The interphase percolation model was utilized to account for the enhanced interfacial load transfer efficiency by covalent grafting and weaken formation of the interphase zone by agglomeration. Through homogenization analysis of the degree of agglomeration for each grafting ratio, we concluded that the highly grafted interface offsets the negative effects of nanoparticle clustering. The proposed multiscale framework was validated against existing experimental data, which implies that this approach can be used effectively for the design of grafted nanoparticle-reinforced polymer matrix composites.